QUOVADIS LAB SCHOOL REGULATION POLICY IN LPTK - Bestari, Prayoga (Universitas Padjadjaran, 2020)
All laboratory schools in the LPTK (Teacher Training Institute) are still in trouble now Â¸ so it certainly demands a solution from the public policy dimension. All labschools under the LPTK are all private, whereas the LPTK is a state. This was experienced by UPI (Universitas Pendidikan Indonesia), UNJ (Jakarta State University), UNP (Padang State University), UNDIKSA (Ganesha Education University) and other LPTKs that have Labschool. Until now Labschool has double accountability and responsibility, namely to the LPTK itself and to the Education Office. So in practice there are often disagreements and miscoordination in governance. So demand a better solution. The main problem; how regulations must be built? This research has the advantage for LPTK as an institution providing teaching staff to have various alternative regulations that must be developed. This research approach uses a qualitative approach with the method of â€œpublic policy analysisâ€ and comparative studies. Focusing on regulations that should bridge the publicâ€™s expectations regarding the status of laboratory schools. The results showed: 1) Laboratory School Regulation still needs to be improved so that it is synergistic with the Ministry of Education and Culture regulations as the LPTK laboratory school; 2) The need for academic studies and political-strategic efforts in the Ministry of Education and culture with the Ministry of Finance to issue special regulations on the status of Labschool under the LPTK.